Pembangunan Rumah Yang Dilakukan Masyarakat Di Bantaran Kali Anafre Kota Jayapura - Asri Syahfitri; Muhamad Yusuf; Safiudin Safiudin; Amri Amri; Rachmad Surya Muhandy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The Purpose of writing this reasearch is to comprehensively describe the neglect of the construction of residential houses by the people on the banks of the Anafre river, Jayapura City. This type of research is using a qualitative method, using a social phenomenological paradigm, to data analysis using a flow model. The study's findings, the construction of dwellings on the Anafre River's banks is an endeavor by inhabitants to acquire a residential house. Many others have copied the government and private buildings that have enlivened the growth on the banks of the Anafre River. Residential house building is done permanently or semi-permanently depending on the demands of the occupants. Without licensing certificates, giving up customs and building permissions for buildings on the Anafre River's banks violates current legislation; these letters are proof of physical and legal facts. The convenience of the Jayapura City BPN in the form of a certificate management policy based on the submission of a recommendation letter from the Ministry of PUPR of Jayapura City, which is in violation of Government Regulation No. 38 of 2011 concerning the River. Many locals are unaware of the convenience of Jayapura City BPN housing on the banks of the Anafre River, which is placed behind the Paldam housing (army settlement), so that civilians building houses in the area feel safe from eviction.